INNOVATIVE STRATEGIES FOR DEVELOPING CORPORATE CULTURE AMONG FUTURE PRESCHOOL EDUCATION SPECIALISTS - Z.M. Zarifova (International Journal of Literature and Language Studies, 2026)
This article examines innovative strategies for developing corporate culture among future preschool education specialists. In the context of rapid expansion and modernization of preschool education in Uzbekistan, the professional preparation of future educators requires more than subject knowledge and pedagogical techniques. It also requires corporate culture competence: the integrated ability to understand, share, reproduce, and improve the values, norms, communication styles, ethical standards, and innovation practices of an educational organization. The study is designed as a conceptual and documentary review supported by secondary statistical analysis. It draws on organizational culture theory, competence-based education, early childhood education quality research, and current data on the preschool education sector in Uzbekistan. The results show that corporate culture competence can be structured around six interrelated components: value-ethical orientation, institutional identity, communication and collaboration, innovation readiness, legal-administrative literacy, and reflective self-regulation. Based on these components, the article proposes a set of innovative strategies: values-based onboarding, project-based learning, simulation and role-play, practicum partnerships, digital portfolios, peer mentoring, service learning, learning communities, and competency-based assessment. The article argues that these strategies should be integrated into university curricula, teaching practice, and institutional partnerships with preschool organizations in order to prepare future specialists for child-centered, inclusive, ethical, collaborative, and innovation-ready professional environments.